Formulation and characterisation of polyherbal anti-acne gel containing Citrus aurantifolia (Christm.) Swingle and Aloe barbadensis Mill. extracts - Hin, Kuai Fiong (2023)
Acne vulgaris or common acne affects teenagers the most. Acne vulgaris is a skin disorder that occurs when dead cells, oil, and bacteria including Propionibacterium acnes, Staphylococcus aureus and Staphylococcus epidermidis clog hair follicles. Medicinal plants are used to treat acne and are safer with less side effects, such as skin irritation. Furthermore, the demand for halal herbal formulations is currently very high on the global market. However, prior research had shown that treating acne by applying Citrus aurantifolia (Christm.) Swingle juice, also known as key lime juice to the skin immediately would flow off upon application. In addition, only a single plant, C. aurantifolia, was employed in an anti-acne gel formulation to treat acne has no synergistic therapeutic effect and does not boost up effectiveness due to the inadequacy of their active bioactive compounds. Moreover, the effects of applying modern treatments (thermal and non-thermal) on anti-acne gel formulation are still unknown. Therefore, the objective of this study is to formulate a polyherbal anti-acne gel containing C. aurantifolia and Aloe barbadensis Mill., also known as Aloe vera. This study is also to characterise the formulated polyherbal anti-acne gel for its physicochemical properties, to investigate the efficacy of the best formulated gel in-vitro permeation study as well as the effects of modern processing treatments on the best formulated polyherbal anti-acne gel storage stability. The phytoconstituents found in plant extracts and their antibacterial activity against S. aureus were also analysed. After plant extracts discovery, gel formulations with varying concentration of plant extracts, and excipients were prepared along with compatibility studies. Various parameters like colour, odour, homogeneity, phase separation, consistency, washability, pH, spreadability, viscosity, extrudability, drug content, antibacterial activity, stability, particle size, in-vitro permeation and compared with a commercial herbal formulation were investigated. Subsequently, the best formulated polyherbal anti-acne gel had been given modern treatments using high-pressure processing and microwave pasteurisation. The results showed that gel formulation containing plant extracts of C. aurantifolia and A. barbadensis as well as the excipients Carbopol 940, methylparaben, propylparaben, propylene glycol-400, triethanolamine and water was found optimum for all the parameters. It has a synergistic effect on antibacterial activity and was comparable to the commercial herbal formulation. However, high-pressure processing and microwave pasteurisation are not preferable treatments options to substitute the paraben in gel formulation. It is concluded that the formulation of a washable and skin-permeable polyherbal anti-acne gel containing C. auranfolia and A. barbadensis has high potential for halal cosmetics product development.